Structural Characterization and Antioxidant Activity in Vivo of Polysaccharides from the Leaves of Hippophae rhamnoides L. - Niannian SONG; Yuxin YI; Xiaoping ZHANG; Bo YANG; Mangsier SAINAWAER; Abuduwaili AYITUXUN (Shipin gongye ke-ji)
This paper as the leaves of Xinjiang Hippophae rhamnoides L. was the research object, and the isolation, structure elucidation, and antioxidant activity in vivo of the polysaccharides from the leaves of Hippophae rhamnoides L. (Hippophae rhamnoides leaf polysaccharide, HRLP) were performed. HRLP were extracted by water extraction and alcohol precipitation method, and homogeneous polysaccharide (HRLP-2) was obtained through DEAE-650M anion exchange column chromatography. The structure of HRLP-2 was identified based on the analysis of liquid chromatography, gas chromatography, UV, infrared spectroscopy, circular dichroism, Congo red experiment, as well as partial acid hydrolysis, periodate oxidation, and Smith degradation methods. Meanwhile, the antioxidant activity in vivo of HRLP was evaluated. The results showed that HRLP-2 was a homogenous polysaccharide composed of rhamnose, arabinose, xylose, mannose, glucose, and galactose with a molar ratio of 10.26:49.37:3.09:2.24:4.50:30.53. Among them, the backbone of HRLP-2 was probably composed of galactose and arabinose, while rhamnose, arabinose, and glucose were for terminals or branched chains. Congo red test results showed that HRLP-2 had a triple helix structure. Compared with the model group, the total superoxide dismutase, glutathione peroxidase, and catalaseactivities of HRLP in the medium dose group were significantly increased (P<0.05), while the content of malondialdehyde was significantly decreased (P<0.05). The HE staining results indicated that HRLP had protective effect on liver and kidney tissue cells and structure damage in mice. The medium dose group of HRLP could increase the number of gut microbiota species in mice and promote the synthesis of short-chain fatty acids in the body. In a word, HRLP may exhibit antioxidant activity by improving oxidative stress and gut microbiota in D-galactose-induced mice. This study provides a reference for the comprehensive utilization of Hippophae rhamnoides L. resources and the structure-activity relationship of Hippophae rhamnoides L. polysaccharides.